Ensembl Genomes 2022: an expanding genome resource for non-vertebrates. Issue Volume 50:Issue D1(2022) (13th November 2021) - Yates, Andrew D; Allen, James; Amode, Ridwan M; Azov, Andrey G; Barba, Matthieu; Becerra, Andrés; Bhai, Jyothish; Campbell, Lahcen I; Carbajo Martinez, Manuel; Chakiachvili, Marc; Chougule, Kapeel; Christensen, Mikkel; et al.
Abstract: Ensembl Genomes (https://www.ensemblgenomes.org ) provides access to non-vertebrate genomes and analysis complementing vertebrate resources developed by the Ensembl project (https://www.ensembl.org ). The two resources collectively present genome annotation through a consistent set of interfaces spanning the tree of life presenting genome sequence, annotation, variation, transcriptomic data and comparative analysis. Here, we present our largest increase in plant, metazoan and fungal genomes since the project's inception creating one of the world's most comprehensive genomic resources and describe our efforts to reduce genome redundancy in our Bacteria portal. We detail our new efforts in gene annotation, our emerging support for pangenome analysis, our efforts to accelerate data dissemination through the Ensembl Rapid Release resource and our new AlphaFold visualization. Finally, we present details of our future plans including updates on our integration with Ensembl, and how we plan to improve our support for the microbial research community. Software and data are made available without restriction via our website, online tools platform and programmatic interfaces (available under an Apache 2.0 license). Data updates are synchronised with Ensembl's release cycle.